The Effect of Swimming Exercise on Memory Impairment and Inflammatory Cytokines Caused by Lipopolysaccharide Injection in Male Rats - Torabi, Farnaz; Khazaee, Khadijeh; Mohammadi, Mohammad (Health Nexus, 2024)
Memory is a fundamental human ability that enables the nervous system to encode, store, and retrieve various types of information. The aim of this study was to examine the effect of swimming exercise on memory impairment and the inflammatory cytokines TNFα and IL1 caused by lipopolysaccharide injection in male rats. In this study, 40 NMRI mice, approximately 70 days old and weighing 23 ± 1 grams, were used. The mice were randomly divided into four groups: a control group (no exercise with saline, no exercise with lipopolysaccharide) and an experimental group (exercise with saline, exercise with lipopolysaccharide). The training program included two phases of swimming: an adaptation phase and a swimming phase. The adaptation phase consisted of three 10-minute sessions with a 10-minute rest interval between each session. The duration of swimming was progressively increased from 20 minutes in the second week to 30 minutes in the third week. The data collected were analyzed using SPSS software with a two-way analysis of variance. The findings of this study demonstrated that swimming significantly reduced the levels of TNFα and IL1 in male rats (p